Demographic Characteristic Of Burn Mortality And Its Relation To Tangential Excision At Burn Unit Of Cipto Mangunkusumo National General Hospital - Wardhana, Aditya; Kurniasari, Dhita (Lingkar Studi Bedah Plastik Foundation, 2018)
Background: Burn injury is considered as major problem because of high mortality and morbidity. One of the several managements to decrease the mortality rate is wound excision. This study aimed to describe the characteristics of burn mortality in our burn unit and its association with timing of tangential excision. Method: We collect data of burn patients who died in 2016 at Burn Unit of Cipto Mangunkusumo Hospital. We investigate the association of mortality and timing of tangential excision. The data were compared with other studies from online databases. Result: Thirty-four burn patients died at RSCM Burn Unit from January - December 2016. 13 patients underwent early tangential excision, the rest had delayed or no tangential excision. Only length of stay (LOS) has statistically significant result. The early tangential excision group has significantly longer median LOS (p=0.003) compared to delayed tangential excision. From five relevant studies, three studies had higher mortality in early tangential excision group compared to delay group but fewer complications and shorter LOS. Two studies reported a significant reduction in mortality in early tangential excision group while culture positive wounds were more frequent in the delay group. Conclusion: Mortality in our patients in early tangential excision group is fewer than the delayed one. The early tangential excision group has longer length of stay compared to delay tangential excision. Although there are pros and cons from the literature review, we suggest that early tangential excision should be done in burn patients.